Studi Fenomenologi: Pengalaman Ibu dengan Anak Tunagrahita di Sekolah Luar Biasa Negeri Tompokersan, Lumajang - Munir, Zainal; Sholehah, Baitus; Hasanah, Nur Hovifatul (Universitas Nurul Jadid, 2024)
Intellectual disability (tunagrahita) is a condition that poses significant challenges when experienced by children, characterized by intellectual impairment with an Intelligence Quotient (IQ) below the average. Children with intellectual disabilities face difficulties in self-care, communication, and adapting to their environment. This study aims to explore the experiences of mothers raising children with intellectual disabilities at SLBN Tompokersan, Lumajang. The study used a qualitative method with a phenomenological approach to gain an in-depth understanding of lived experiences from the perspective of the participants, involving five respondents. The findings revealed five main themes: parenting methods for children with intellectual disabilities, the emotional experiences of mothers, changes in parental (mother's) mindset after having a child with intellectual disabilities, lack of parental knowledge in caregiving, and the level of children's dependence on their mothers or others. A key takeaway from this study is that the different experiences of mothers in raising children with intellectual disabilities significantly influence their parenting styles.